Flemingia Strobilifera– An Updated Review on its Pharmacognostic and Pharmacological Properties - Sahu, Asmit; Dubey, Neha; Satapathy, Trilochan; Pandey, Ravindra Kumar; Shukla, Shiv Shankar; Gidwani, Bina (Current Nutrition & Food Science, 2025)
BackgroundOur health care system greatly benefits from the use of old medical techniques. In Ayurvedic medicine to improve manhood, Flemingia strobilifera (Lam.) is utilized as an herb. The Fabaceae family, which includes Flemingia strobilifera (Palas), is widely cultivated throughout India. There are more than forty species of Flemingia throughout the globe; out of which 15 species of this genus are in India.ObjectiveTo learn more details about this plant and various species of Flemingia, specifically the chemical makeup of the plant, its species, and/or its elements, traditional and medical uses for the plant. This review article also focuses on the origin, history, classification, phytochemistry, morphology, microscopy, and pharmacological aspects.MethodsA detailed and extensive literature survey through research findings, review articles, Google sources, database etc. was done to explore the aspect of Flemingia species for its various physical, chemical, pharmacological, phytochemistry and related fields.ResultsOur findings report that several representatives of this genus have been employed as vermifuges and remedies for fever, diarrhea, indigestion in traditional medicine. The plants anthelmintic, anticancer, antirheumatic, antiinflammatory, antioxidant and antihistaminic effects are well documented. According to literature reports, the chemical constituents of this genus are flavonoids, glycosides, chalcones, epoxy chromenes, and pterocarpans. Rural and ethnic people regularly use this plant to treat a range of diseases.ConclusionResearch on Flemingia strobilifera has a bright future thanks to its strong natural origin. The uniqueness and usefulness of Flemingia strobilifera was obscured. In future, many more potential of Flemingia could be investigated in combination with other herbs.
Keywords: Traditional uses